The handmaid's tale - Atwood, Margaret Eleanor, 1939- (New York : Anchor Books, 1998)
Set in the near future, America has become a puritanical theocracy and Offred tells her story as a Handmaid under the new social order.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Wilson's Senior High School.
Young Adult
Keywords: Man-woman relationships -- Fiction; Misogyny -- Fiction; Religion -- Fiction; Women -- Fiction; Dystopias; Man-woman relationship -- Fiction; Religion -- Fiction; Women -- Fiction; Fantastic fiction